The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3832/ifor1885-009
|View full text |Cite
|
Sign up to set email alerts
|

Clonal structure and high genetic diversity at peripheral populations of Sorbus torminalis (L.) Crantz.

Abstract: Knowing the level of genetic diversity and structure in marginal plant populations is essential for managing their genetic resources. This is particularly important for rare scattered tree species, such as Sorbus torminalis (L.) Crantz. We investigated the genetic diversity and its spatial distribution in peripheral populations of S. torminalis. As the species is known to reproduce vegetatively, we also evaluated clonal structure within populations. Using 13 nuclear microsatellite loci designed in two multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 72 publications
(91 reference statements)
2
14
0
Order By: Relevance
“…Our results thus contrast the commonly proposed theory that the peripheral populations have less genetic diversity when compared to central populations (Rasmussen and Kollmann 2007;Arnaud-Haond et al 2006;Yeh and Layton 1979). Similar trends have been previously reported in other woody species (Gapare et al 2005;Muir et al 2004;Jankowska-Wroblewska et al, 2016;Yakimowski and where the genetic diversity was not different between the peripheral and core populations. In a review of population genetic studies, 64% of 81 studied plant species showed lower genetic diversity in the peripheral populations, and 33% of 37 studied plant species conformed to the hypothesis that the peripheral populations were genetically differentiated from their central counterparts.…”
Section: Genetic Diversity Of Prunus Avium At Its Northern Parts Of Ssupporting
confidence: 82%
“…Our results thus contrast the commonly proposed theory that the peripheral populations have less genetic diversity when compared to central populations (Rasmussen and Kollmann 2007;Arnaud-Haond et al 2006;Yeh and Layton 1979). Similar trends have been previously reported in other woody species (Gapare et al 2005;Muir et al 2004;Jankowska-Wroblewska et al, 2016;Yakimowski and where the genetic diversity was not different between the peripheral and core populations. In a review of population genetic studies, 64% of 81 studied plant species showed lower genetic diversity in the peripheral populations, and 33% of 37 studied plant species conformed to the hypothesis that the peripheral populations were genetically differentiated from their central counterparts.…”
Section: Genetic Diversity Of Prunus Avium At Its Northern Parts Of Ssupporting
confidence: 82%
“…As expected from a largely outbreeding tree, S. torminalis has been found to be genetically diverse within and between populations with strong gene flow (Demesure et al 2000a;Oddou-Muratorio et al 2001aBednorz & Krzakowa 2002;Bednorz, Myczko & Kosi nski 2004Oddou-Muratorio, Klein & Austerlitz 2005;Rasmussen & Kollmann 2004bHoebee et al 2006Hoebee et al , 2007Angelone et al 2007;Espahbodi et al 2008, Jankowska-Wroblewska et al 2016. Sorbus torminalis in Britain has a lower genetic diversity than the other two common sexually reproducing diploid species, S. aria and S. aucuparia (Proctor, Proctor & Groenhof 1989;Chester et al 2007) and lower than S. torminalis in mainland Europe: Chester et al found that pollen exchange shows two main patterns: preferential mating between neighbouring trees from local pollen dispersal with a mean of 6 pollen donors providing the pollen cloud around a given tree, and also long-distance pollen movement of up to 2Á5 km.…”
Section: Floral and Seed Charactersmentioning
confidence: 73%
“…, Jankowska‐Wroblewska et al . ). Sorbus torminalis in Britain has a lower genetic diversity than the other two common sexually reproducing diploid species, S. aria and S. aucuparia (Proctor, Proctor & Groenhof ; Chester et al .…”
Section: Floral and Seed Charactersmentioning
confidence: 97%
“…On the other hand, extensive dispersal and immigration would weaken FSGS over generations. Therefore, investigating the pattern of FSGS and how it varies between generations provides insight into the intensity and spatial scale of gene dispersal and other fundamental aspects of species' biology, such as the mating system (Segelbacher et al 2010) or clonality (Dering et al 2016;Jankowska-Wroblewska et al 2016). Knowledge of the scale of gene dispersal within populations of species is a crucial information for the design of a conservation strategy that will be effective for the maintenance of genetic diversity of the species.…”
Section: Introductionmentioning
confidence: 99%